Critical analysis of polyindole and its composites in supercapacitor application - Harish Mudila (Materials for Renewable and Sustainable Energy, 2019)
Abstract Polyindole-based hybrid composites are being recognized as a promising candidate to be used in energy storage field along with other conjugated organic polymers. Polyindoles themselves are affected with low electrical and electrochemical conductivity; nevertheless, high redox activity, tunable electrical conductivity, significant thermal stability, slow degradation rate, and possible blending property give them upper hand to be used as a good contender. Certain factors viz. electrolyte, concentration, morphology, pH, temperature, etc., are major components affecting performance of Polyindole and its composites. This assessment recapitulates the position of Polyindole and its hybrid composite to be used as energy harvest material; in addition, this evaluation also pronounces the future aspect of the hybrids.